Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Solve by substitution. X = 2y - 4 2x – 3y = -3 Answer​

Sagot :

Answer:

Y= 5

X=6

Step-by-step explanation:

Plug in the equation and you get

2(2y-4)-3y=-3

which gives you y=5

Plug in y to get x=2•5-4

Which gives you 6 for x

Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.